POST-PANDEMIC VIRTUAL MICE ACTIVITIES - Ni Putu Diah Pitria; Ni Putu Dewi Primadini Putri; Ni Wayan Rika Ardiani; Devia Preopi Arika Putri (UHN IGB Sugriwa Denpasar, 2023)
The COVID-19 pandemic has led to social restrictions and the spread of the virus, affecting in-person gatherings and resulting in changes in the world of the tourism industry, particularly in the MICE sector, which has shifted to virtual events. The MICE industry itself encompasses organizers and suppliers who manage and deliver all aspects of an event. Professional MICE events comprise several aspects of large-scale gatherings, such as travel agencies, creative design services, catering, marketing, and logistics. MICE is a business activity that can provide benefits, especially in the tourism sector. In this study, MICE activities are analyzed from the perspective of virtual events using a literature review research method, which is a qualitative research approach that gathers data from various sources. The results of this research have revealed a new innovation in the form of virtual MICE activities, which have received both positive and negative responses from the public due to considerations of the positive and negative impacts of virtual MICE activities on society.